Synchronous Detection of BPV and BVDV with Duplex Taqman qPCR Method - Gong, Zhuan-di; Shen, Xiao-yun; Liang, Hao-qin; Geng, Jin-jing; Li, Qion-yi; Feng, Ruo-fei; Wei, Suo-cheng (Acta Scientiae Veterinariae, 2019)
Background: Bovine parvovirus (BPV) and bovine viral diarrhea virus (BVDV) are commonly etiologies causing diarrhea in dairy herds. BPV is a member of bocaparvovirus genus with a non-enveloped capsid. BVDV, belonging to Pestivirus genus in Flaviviridae, possesses a single-stranded RNA, and is classified into BVDV-1 and BVDV-2 genotypes according to the 5’UTR sequence. 21 genetic groups of BVDV-1 and four groups of BVDV-2 have been found. Diagnosis of viral diarrhea is often relied on virus detection by isolation or detection of serum antibody. The main objective of the present study was to establish a duplex real time PCR (qPCR) based on Taqman probe to detect synchronously BPV and BVDV. Materials, Methods & Results: TaqMan probe and primers were designed and synthesized from the sequences of conserved 5′ - untranslated regions (5′ UTR) of Haden strain of BPV and NADL strain of BVDV. The cDNAs were transcribed in vitro to make standard curves before optimizing the assay. DNA/PCR products were ligated into pMD18-T vector, and then used to transfer BL-21 competent cells to acquire the recombinant plasmids of pMD18-T-BPV and pMD18-T-BVDV. Optimum reaction conditions were comparatively selected. The sensitivity, specificity and reproducibility of TaqMan probe qRT-PCR were evaluated respectively. The results showed the concentrations of pMD18-T-BPV or pMD18-T-BVDV were 2.0 × 1010 DNA copies/μL, respectively. A duplex Taqman qPCR method was developed by optimizing the amplification conditions to simultaneously detect BPV and BVDV. The assay targets at highly conserved VP2 gene of BPV and 5′ UTR gene of BVDV. This qPCR assay was assessed for specificity and sensitivity using DNA of BPV and cDNA of BVDV. For clinical validation, 308 samples were tested from clinically diarrhea calves. The results showed that optimum annealing temperature was achieved in 43.2 ℃ fro duplex BPV and BPIV. Dynamic curves and standard curves were created following amplification of recombinant plasmids using the optimized duplex Taqman BPV and BVDV, with an amplification efficiency of 95.69%. Duplex Taqman qPCR could only detect DNA of BPV and cDNA of BVDV with a strong specificity. The detection limitation was as low as 2.0 × 102 copies/μL of pMD18-T-BPV plasmid and 2.0 × 101 copies/μL for pMD18-T-BVDV plasmid, respectively. Sensitivity of detection was 100-fold higher than conventional PCR. Duplex Taqman qPCR had excellent repeatability or stability with less than 1.2% of intra-assay and inter-assay. 35 and 47 positive feces samples were identified using duplex Taqman qPCR in comparison to 30 and 42 positives for universal PCR, respectively. Discussion: The bovine viral diarrhea virus (BVDV) is a key pathogenic factor in bovine diarrhea. Currently, few effective measures are available for the treatment or prevention for BVDV and BPV infections in animals. The technique was proven to be repeatable and linear over a range of at least 5 magnitudes, from 101 to 105 RNA/DNA copies, thus ensuring an accurate measurement of BPV DNA and BVDV RNA loads in clinical samples. In conclusion, a duplex Taqman qPCR was established for detecting simultaneously BPV and BVDV. Taqman qPCR method was rapid and specific assay. This assay was 100-fold sensitive than conventional PCR. It will be propitious to rapidly and differentially diagnose pathogens of viral diarrhea of dairy farms. Taqman qPCR method was rapid and specific assay and had a sensitivity of 2.0 copies/μL.